2000
DOI: 10.1001/archpsyc.57.5.471
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Measure of the Frontal and Temporal Lobe Regions in Schizophrenia

Abstract: Background: Previous research has provided evidence for brain abnormalities in schizophrenia, but their relationship to specific clinical symptoms and syndromes remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
148
2
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(174 citation statements)
references
References 67 publications
18
148
2
6
Order By: Relevance
“…Although much of the methodology stayed constant between the current and previous studies, caution must be taken in interpreting results from combined studies that were performed at different times with differing methodologies. Sanfilipo et al (2000) also found an association between white matter volume and negative symptoms in schizophrenic subjects. They reported that the white matter reduction was most severe in the orbitofrontal region.…”
Section: Discussionmentioning
confidence: 67%
“…Although much of the methodology stayed constant between the current and previous studies, caution must be taken in interpreting results from combined studies that were performed at different times with differing methodologies. Sanfilipo et al (2000) also found an association between white matter volume and negative symptoms in schizophrenic subjects. They reported that the white matter reduction was most severe in the orbitofrontal region.…”
Section: Discussionmentioning
confidence: 67%
“…Previous MRI work reported smaller STG volume was associated with more positive symptoms in schizophrenia but that no significant correlations emerged among the SPD patients (Takahashi et al 2006a). Other work indicates prefrontal and temporal gray matter volume is unrelated to various clinical symptoms in schizophrenia while reduced white matter volume in these regions is associated with negative symptoms (Sanfilipo et al 2000). Differences in patient characteristics may explain these differing findings.…”
Section: Discussionmentioning
confidence: 92%
“…The literature has multiple reports of lower white matter volumes in schizophrenia compared with matched normal controls (Breier et al 1992;Buchanan et al 1998;Cannon et al 1998;Sanfilipo et al 2000;Bartzokis et al 2001). Technical factors may make such observations less likely in the usual axial analysis of the brain used in imaging studies if the differences are localized to frontal and association regions (Bartzokis et al 2001), the only areas where post mortem data indicates that myelination continues into adulthood (Yakovlev and Lecours 1967).…”
Section: Myelination and Brain Functional Synchronymentioning
confidence: 99%